2008
DOI: 10.2495/ht080171
|View full text |Cite
|
Sign up to set email alerts
|

Air curtains of open refrigerated display cases revisited: a new technique for infiltration rate measurements

Abstract: Air curtains are created in open refrigerated vertical display cases for creating an invisible barrier between the cold air inside and the warm air outside the case. A systematic approach is developed to minimize the entrainment and infiltration of warm air into the case by optimizing the performance of an air curtain through adjusting pertinent flow parameters and case geometry. A modular display case was manufactured for the parametric studies. In this modular display case the geometry and flow parameters we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…There are several applications of this concept that aim to avoid contaminant spreading, such as: an operating room [7,[14][15][16][17][18][19], a tobacco smoke control [20,21], the protection of art works in museums and of cultural heritage [22,23], and open refrigerated display cabinets [24,25]. Several studies about air curtain efficiency have been conducted on these applications.…”
Section: (A) (B)mentioning
confidence: 99%
“…There are several applications of this concept that aim to avoid contaminant spreading, such as: an operating room [7,[14][15][16][17][18][19], a tobacco smoke control [20,21], the protection of art works in museums and of cultural heritage [22,23], and open refrigerated display cabinets [24,25]. Several studies about air curtain efficiency have been conducted on these applications.…”
Section: (A) (B)mentioning
confidence: 99%
“…The study of the use of air curtains to avoid contaminant spreading has been reported, for tobacco smoke control, 17,18 for operating rooms, 7,[19][20][21][22][23][24] in offices, 25 for protection of art works in museums and of cultural heritage, 26,27 in personalized air curtains, 28 in open refrigerated display cabinets [29][30][31] and in public transportation. 32 The studies on the performance of air curtains have been based on CFD models, 25,27,28,31,[33][34][35][36] on semi-analytical models, 16,37 and on experiments.…”
Section: Introductionmentioning
confidence: 99%
“…The solid lines denote the flow that will eventually enter the RAG while the short dashed lines symbolize the flow that will enter the ambient. Results of Navaz et al (2002) and CFD results of Amin et al (2008), performed by Fluent commercial code, indicated that almost all the flow that leaves the CV and entering the ambient, exits from the lower part of the vertical boundary close to the RAG, while almost all the entrainment occurs from the rest of the outerside vertical boundary (Fig. 3a).…”
Section: Relation Between Infiltration Rate and Tracer Gas Concentrationmentioning
confidence: 98%
“…Consequently, the need to improve the design of the ORDCs has been felt from decades ago and much effort has gone into developing more cost effective and energy efficient systems. Air curtain research has ranged from analytical studies (Hayes and Stoecker, 1969) to experimental (Field et al, 2002;Navaz et al, 2002Navaz et al, , 2005Rouaud and Havet, 2006;Amin et al, 2008) and computational (Stribling et al, 1997;Cortella et al, 2001;Axell and Fahlen, 2002;Navaz et al, 2005;Foster et al, 2005;Rouaud and Havet, 2006) investigations. One of the conventional methods for the infiltration measurement is based on collection of condensate dripping off the evaporator of the refrigeration system .…”
Section: Introductionmentioning
confidence: 98%